Content-Based Instruction as an Effective Strategy for Enhancing Maritime English Skills in Maritime Education - Sulistiono, Agus; Sumarta, Ryan Puby; Hafita, Yuniar Ayu; Hasanudin; Kariadi, Mustasyfa Thabib (GoAcademica Research & Publishing, 2024)
This study examines the effectiveness of Content-Based Instruction (CBI) in enhancing Maritime English proficiency among cadets at Sorong Merchant Marine Polytechnic. A quantitative approach was used, employing pre-test and post-test evaluations, along with a questionnaire to assess cadets’ language development and perceptions. The study involved 24 fourth-semester cadets in the Nautical Studies program. Results showed a significant improvement in Maritime English proficiency, with average test scores increasing from 69.7 (pre-test) to 95.7 (post-test), demonstrating a substantial 26-point improvement. Statistical analysis (paired t-test, p < 0.05) confirmed the significance of this improvement. The questionnaire results indicated that cadets viewed the CBI approach as highly effective, with an average satisfaction score of 4.5 out of 5. This research highlights the success of CBI in bridging the gap between language acquisition and real-world maritime contexts, suggesting it could serve as a valuable model for Maritime English instruction in similar educational settings. The findings support the integration of CBI into maritime curricula to better prepare cadets for the linguistic and operational demands of the global maritime industry.